PERSEPSI DAN SIKAP MAJELIS ULAMA INDONESIA (MUI) TERHADAP SOUND HOREG SERTA KRITIK TERHADAP BUDAYA LOKAL - Annisa Rahma Pratiwi (Jurnal Jendela Hukum, 2025)
The phenomenon of using high-capacity sound systems known as “sound horeg” at entertainment events, folk festivals, or commercial activities in Indonesia has sparked various debates. Its existence often causes controversy among Indonesians, especially after the issuance of a fatwa declaring it haram by the MUI. The MUI, as a religious organization that has a major impact in providing perspectives on social and community issues or polemics, has also responded to the prohibition and practice of using sound horeg. The purpose of this study is to analyze the MUI's views and attitudes towards the prohibition of sound horeg and to evaluate the impact of these attitudes on the preservation of local culture in Indonesia. This research applies a document analysis method by utilizing official MUI statements and relevant regulations, as well as conducting a comprehensive literature review on the issue of sound horeg, religious social dynamics, and local culture in Indonesia. Keywords : Sound Horeg, Social, Cultural Critique.